Compatibility of Maximum-Containment Virus–Inactivation Protocols With Identification of Bacterial Coinfections by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry. (4th July 2018) - Matson, M Jeremiah; Stock, Frida; Shupert, W Lesley; Bushmaker, Trenton; Feldmann, Friederike; Bishop, Wendy B; Frank, Karen M; Dekker, John P; Chertow, Daniel S; Munster, Vincent J
Abstract: Diagnostics and research analyses involving samples containing maximum-containment viruses present unique challenges, and inactivation protocols compatible with downstream testing are needed. Our aim was to identify a validated viral inactivation protocol compatible with bacterial identification by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). We assessed a panel of bacteria with 6 validated maximum-containment virus–inactivation protocols and report that inactivation with TRIzol or γ-irradiation is compatible with MALDI-TOF MS. The availability, simplicity, and rapidity of TRIzol inactivation make this method the more suitable choice.